Multi-scale Multi-physics Phase-field coupled Thermo-mechanical approach for modeling of powder bed fusion process - Darabi, Roya; Azinpour, Erfan; Reis, Ana; de Sa, Jose Cesar (Applied mathematical modelling, 2023)
•A multi-physics thermomechanical phase-field Allen-Cahn formulation is built for studying powder bed fusion processes.•The underlying physics of the phase changes in the powder bed fusion is exposed.•An adaptive mesh refinement strategy is used to capture the melting and solidification frontiers.•Automatic scaling is used to overcome different orders of magnitude of the field variables.•The effect of the phase-field length scale on the temperature, melt pool geometry and stress distributions is explored. The present study investigates the thermomechanical simulation of powder bed fusion (PBF) process, focusing on the characterization of the melt pool. With the aim of comprehensively understanding the complex multi-physics phenomena inherent to the PBF process, our objective is to establish a robust and refined computational framework that is capable of systematic evaluation of the dynamic evolution of the melt pool geometry and temporal characteristics across the various stages of its formation. For this purpose, the Allen-Cahn phase field formulation is integrated with the elastoplastic material model based on J2 plasticity theory and the model implementation is conducted based on a finite element method (FEM) framework using the Multi-physics Object-Oriented Simulation Environment (MOOSE). As an objective, the model tends to depict the intricate, nonlinear, and non-equilibrium nature of the melt pool, encompassing multi-physics process of the PBF, while assuming powder particles as a homogenized continuum medium and neglecting complex interactions between the particles and their surroundings. This includes the separation of geometry into two domains (i) the powder layer and (ii) the substrate, the melting and solidification of the material, the phase-changing process, and the resulting induced distortion and residual stresses. Additionally, the model incorporates a phase indicator to account for the degree of solidification or consolidation of powder, whose evolution describes diffusion, solidification and shrinkage phenomena. This approach enables the tracking of the movement of the melting front of the metallic material induced by a heat source, effectively dividing the domain into regions of soft and hard solid states with a diffusive interface in between. Furthermore, to enhance the model's fidelity, an adaptive mesh refinement (AMR) strategy is employed to precisely capture important aspects of the phase changing process, such as characteristics of the solidification front and powder melting. To assess the model's performance, it is tested by simulating the processing of a three-dimensional Inconel 625 thin plate, as well as a benchmark example, where the influence of parameters such as temperature and phase change on the mechanical response of the system during the solidification process is elucidated.